2018
DOI: 10.1002/hbm.24286
|View full text |Cite
|
Sign up to set email alerts
|

Impact of frequency of internet use on development of brain structures and verbal intelligence: Longitudinal analyses

Abstract: Excessive internet use is shown to be cross sectionally associated with lower cognitive functioning and reduced volume of several brain areas. However, the effects of daily internet use on the development of verbal intelligence and brain structures have not been investigated. Here, we cross sectionally examined the effects of the frequency of internet use on regional gray/white matter volume (rGMV/rWMV) and verbal intelligence as well as their longitudinal changes after 3.0 ± 0.3 (standard deviation) years in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 56 publications
1
58
0
2
Order By: Relevance
“…Conversely, the most recent study from Takeuchi et al revealed that frequency of internet use was not associated with regional gray matter volume in cross-sectional analyses. However, the longitudinal analysis revealed that frequency of internet use was associated with gray matter reductions in widespread clusters, including the bilateral perisylvian areas, the cerebellum and the subcortical regions (e.g., the hippocampus, the amygdala or the basal ganglia; [16]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, the most recent study from Takeuchi et al revealed that frequency of internet use was not associated with regional gray matter volume in cross-sectional analyses. However, the longitudinal analysis revealed that frequency of internet use was associated with gray matter reductions in widespread clusters, including the bilateral perisylvian areas, the cerebellum and the subcortical regions (e.g., the hippocampus, the amygdala or the basal ganglia; [16]).…”
Section: Discussionmentioning
confidence: 99%
“…There are only two previous longitudinal studies examining the influence of sedentary behaviors (i.e., watching TV and internet use) on gray matter volume in children [15,16]. One study found that watching more TV was associated with greater gray matter volume in the frontopolar and the medial prefrontal areas in cross-sectional and longitudinal analyses, as well as positive associations in areas of the visual cortex using cross-sectional analyses and positive associations in the hypothalamus/septum and the sensorimotor areas in longitudinal analyses [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the Internet's digital distractions and supernormal capacities for cognitive offloading seem to create a non‐ideal environment for the refinement of higher cognitive functions in critical periods of children and adolescents’ brain development. Indeed, the first longitudinal studies on this topic have found that adverse attentional effects of digital multi‐tasking are particularly pronounced in early adolescence (even compared to older teens), and that higher frequency of Internet use over 3 years in children is linked with decreased verbal intelligence at follow‐up, along with impeded maturation of both grey and white matter regions.…”
Section: Conclusion and Directionsmentioning
confidence: 99%
“…Most of these studies collect information on behavioral and neurocognitive characteristics and/or genetic data from a general population. In Japan, there has been a large‐scale cross‐sectional and longitudinal cohort survey targeting children and adolescents . The targets were set to a relatively broad age range (6–18 years).…”
mentioning
confidence: 99%